Designing Household Scale Water Filtering with Two Tubes - Sugiyanto, Sugiyanto; Yudiansyah, Miftahudin; Khasanah, Rizky Anggit Maya Olif Fatul (Proceeding International Conference on Science and Engineering, 2019)
The basic concept of water treatment by filtering is to separate solids or colloids from water using a filter. In the screening process there are two types, namely physics and biology. The particles in the turbid water will be physically retained by the sand layer in the filter. On the other hand, pathogenic bacteria that are retained by the filter will be destroyed by the filter installed. The design process in this paper is a simple process that can be assembled by a small family and the price is quite cheap.